PERANCANGAN DAN PEMBUATAN APLIKASI PERHITUNGAN HARGA POKOK PRODUKSI DENGAN METODE PROCESS COSTING PADA TOKO ROTI âMON DELICE BOULANGERIEâ - Harjono, Vania Christina; Setiawan, Alexander; -, Yulia (Jurnal Infra, 2013)
Mon Delice Boulangerie is a store that working on bakery industry. Nowadays, recording data on Mon Delice Boulangerie is still done in manual way.Â The calculation of production cost price is still calculated manually and that calculationÂ only include that can only includes the cost of materials that is used, while overheads and labor costs have not been included to the calculation. The calculation of the cost of goods manufactured in the manual way would have caused a lot of problems and will affect the benefits for the store.Based on background of that problem, it is designed a system to calculate the cost of production. The process of application system design through severalÂ stages, beginning with survey production system of the bakery, data analysis and designing Data Flow Diagram and Entity Relationship Diagram of the application that will be made. The author used Microsoft Visual Studio .Net 2005 as the programming tool and Microsoft SQL Server as the database of the program. The calculation of the cost of goods manufactured is using Process Costing method.Results that obtained from the application that have been made are able to store all data related to the production, purchasing materials, sales of breads, the calculation of cost of goods manufactured that is calculated automatically, and stock card that can be updated automatically.